Después del “Redoble por Rancas”: tierra, minería y memoria de un pueblo - Flores Bordais, Lourdes Eddy (Universidade Federal de São Carlos, 2018)
This master's thesis presents the historical relationship between the San Antonio de Rancas Peasant Community, located in the Pasco region, in the Central Andes of Peru, with the mining companies that operated and operate in the region from the early years of the 20th century until today. Its title refers to the novel published by Manuel Scorza in 1970 that narrates the peasant organization to recover their communal lands enclosed and privatized by the mining company, since our historical research covers the events after the Massacre of Huayllacancha (1960) until today. Based on the expropriation of land and being, it seeks to account for the contradictory features that mark this relationship and open new horizons in the lives of the people of Rancas. How the Ranqueños, after a direct struggle against mining, would have partially sacrificed their relationship with the land as a natural laboratory and cultural foundation and would have given way to strengthening entrepreneurial and individualistic values sympathetic to mining in the region. Supported by a deep socio-historical analysis, we intend to account for these changes that oscillate between integration and resistance to mining expansion. We maintain that the main source of resistance is mediated by historical memory in the Community; while, in a contradictory manner, the character of its integration into mining capitalism increasingly threatens the non-capitalist forms that maintained for centuries the validity of the common. Finally, we made a general observation from the theoretical complex of Bolívar Echeverría. The method used is oral history and documentary analysis.

Esta tesis de maestría presenta la relación histórica entre la Comunidad Campesina San Antonio de Rancas, localizada en la región de Pasco, en los Andes Centrales del Perú, con las empresas mineras que operaron y operan en la región desde los primeros años del siglo XX hasta la actualidad. Su título hace referencia a la novela publicada por Manuel Scorza en 1970 que narra la organización campesina para recuperar sus tierras comunales cercadas y privatizadas por una empresa minera, pues nuestro recorte histórico abarca los hechos posteriores a la Masacre de Huayllacancha (1960) hasta la actualidad. Tomando como base la expropiación de la tierra y del ser, se busca dar cuenta de los rasgos contradictorios que marcan dicha relación y abren nuevos horizontes en la vida de los ranqueños. Se trata de ver cómo los ranqueños después de una lucha directa contra la minería habrían sacrificado parcialmente su relación con la tierra como laboratorio natural y fundamento cultural y habrían dado paso al fortalecimiento de los valores emprendeduristas e individualistas simpáticas a la explotación minera en la región. Apoyados en un profundo análisis sociohistórico, pretendemos dar cuenta de estos cambios que oscilan entre la integración y la resistencia a la expansión minera. Sostenemos que la principal fuente de resistencia está mediada siempre por la memoria histórica en la Comunidad; mientras que, de manera contradictoria, el carácter de su integración al capitalismo minero amenaza cada vez más las formas no capitalistas que mantuvieron por siglos la vigencia de lo común. Finalmente, realizamos una observación general de los resultados desde el complejo teórico de Bolívar Echeverría y su crítica de la modernidad capitalista. El método utilizado es la historia oral y el análisis documental.
Depois do "Redoble por Rancas": terra, mineração e memória de um povoado
Keywords: Memória; Ethos Barroco; Terra; Mineração; Memory; Baroque Ethos; Land; Mining; Memoria; Tierra; Minería; Rancas; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA RURAL